E-Comic-Based Mathematics Learning: Its Effect on Logical Reasoning and Motivation among Students in Urban and Rural Areas - Angesti Gita Kartika; Ali Shodikin (Didaktik Matematika, 2025)
Many junior high school students perceive mathematics as a difficult subject due to the use of instructional techniques that are less engaging and limited in context. As technology continues to develop, digital mediaincluding e-comicshave become innovative tools for enhancing students motivation and logicalmathematical reasoning. This quasi-experimental study involved 100 eighth-grade students from both an urban school in Surabaya, the capital city of East Java Province, and a rural school in JiwanMadiun, one of the districts in East Java, using a pretestposttest control group design, using a pretestposttest control group design. The experimental and control group from each location as the samples. A questionnaire to measure the students motivation and mathematics logical reasoning questions to assess logical-mathematical reasoning are the instrument. Statistical analysis included regression, Pearson correlation, and ANOVA test. The effect size (R = 0.466) demonstrated the strength of the model. The results revealed that e-comic-based learning significantly improved students motivation and logical- mathematical reasoning, with greater effects observed in urban schools. Furthermore, there was a moderately positive correlation between learning motivation and logical-mathematical reasoning abilities (r = 0.587). These findings suggest that integrating e-comics can effectively enhance learning outcomes while bridging urban-rural educational gaps